THE INFLUENCE OF OBESITY ON CLINICAL AND LABORATORY INDICATORS OF PSORIATIC DISEASE - Yemchenko, Ya.O.; Kaydashev, I.P.; Ishcheykin, K.Ye.; Bezeha, O.V.; Vasylyeva, K.V.; Bolotna, L.A. (World of Medicine and Biology, 2023)
Psoriasis is a chronic, inflammatory, systemic immune-mediated disease of a multifactorial nature in which genetic factors play a dominant role in development. Psoriasis is characterized by an accelerated proliferation of epidermocytes and a violation of their differentiation, immune reactions in the dermis and synovial membranes, an imbalance between pro- and antiinflammatory cytokines, chemokines, and frequent pathological changes in the musculoskeletal system. A close connection between psoriasis and obesity has recently been proven. It is known that in the pathogenesis of psoriasis and obesity, inflammatory processes play a decisive role, which form a vicious circle at the level of the immune system, which must be broken for the successful treatment of these diseases. The results of our study established that dietary obesity in patients with psoriasis leads to metabolic disorders, complicates the course of psoriasis, affects the deterioration of the dermatological index of the quality of life of patients, leads to the ineffectiveness of standard treatment and frequent relapses of psoriatic disease.
Keywords: psoriasis; systemic inflammation; dyslipidemia; insulin resistance